P1513EDEMA SCORE OF CHRONIC KIDNEY DISEASE (CKD) 5D PATIENTS SHOW DIFFERENT CORRELATION WITH NON-CKD PATIENTS AND ARE STRONGLY INFLUENCED BY THE SERUM ALBUMIN VALUE ; PROPENSITY SCORE MATCHING ANALYSIS. (6th June 2020) - Murakami, Takuya; Saito, Osamu; Saito, Takako; Ueno, Koushi; Akimoto, Tetsu; Nagata, Daisuke
Abstract: Background and Aims: Previously studies reported bioelectrical impedance analysis (BIA) method is useful for body fluid evaluation, especially for evaluation of edema in CKD patients. However, it is still unelucidated what factor affects edema score in CKD patients. In this study, we investigated the factors that determine edema score of CKD 5D patients and reported new findings on the differences from non-CKD patients by using propensity score matching analysis. Method: We measured the edema score of 117 CKD 5D patients and 303 non-CKD patients using the BIA method and analyzed the relationship with clinical laboratory factors. The edema score was expressed as the ratio of the total body weight (TBW) to the extracellular water (ECW) and was measured with InBody 20 ® (InBody Japan). All patients with CKD 5D were undergoing hemodialysis and the data were measured immediately after dialysis treatment. Results: There were differences between CKD 5D patients and non-CKD patients in age, sex, and BMI. Since these factors were estimated to affect edema scores, we performed propensity score matching with age and sex, BMI in CKD 5D patients and non-CKD patients. After performing propensity score matching, the differences of age, sex, and BMI between the two groups disappeared. The number of patients became 70 in both groups. By analyzing the model, the edema score of CKD 5D patients indicated significantly higher than that of non-CKD patients (CKD 5D; 0.400±0.012 v. s. non-CKD; 0.389±0.008, P<0.001). Edema score and factor which indicated significant difference by single regression analysis were examined using stepwise multiple regression analysis. As a result, we clarified that muscle mass is the most influential factor (p<0.0001), and age is the next (p=0.025) on edema score in non-CKD patients, however, in CKD 5D patients, serum albumin level is the most influential factor, and no significant influence was found in muscle mass and age (p=0.0006). Conclusion: For CKD 5D patients, the edema score is defined by serum albumin, and serum albumin value has much greater influence than age. It is known that low level of serum albumin is associated with poor prognosis in CKD 5D patients. From these results, it was suggested that edema score could be a better prognostic factor than ageing for CKD 5D patients.